Inovasi Aplikasi “Sayang Warga” dalam Meningkatkan Kemudahan Pendataan Warga oleh Kader di Kota Surabaya - Meiregina, Anisya; Widiyarta, Agus (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
A novelty is needed for government administrators and community development to be more effective and efficient. The Surabaya City Government seeks to provide services in managing information accurately. It is necessary to have the role of the community, namely cadres to contribute in conducting survey services for citizen data collection in order to improve the quality of public services in the city of Surabaya. Information from the survey results can be uploaded via the Sayang Warga application. The purpose of this study is to describe the "Sayang Warga" Application Innovation in increasing the ease of citizen data collection by cadres in the city of Surabaya. This study uses qualitative methods with data collection techniques in the form of interviews, observation and documentation. The theory used in this study is the attribute of innovation according to Rogers in Suwarno (2008) which includes Relative Advantage, Compatibility, Complexity, Triability, and Observability. The results of the study show that the application of the Sayang Warga application in the city of Surabaya can be said to make it easier for cadres to carry out the citizen data collection process. The application of this application also provides benefits in making service easier and does not require a long time, only in its implementation there are still some obstacles in the Sayang Warga application making it difficult to access.